Examining the relationship between ESG performance and financial performance of firms listed on the JSE - Ball, Robert (Department of Finance and Tax, 2021)
This study investigates the relationship between the environmental, social and governance (ESG) performance of South African firms and their corresponding financial performance over the period 2012 to 2019. Operating with an ESG-based mindset has become of increasing importance for firms over the past two decades, as a result of increasing regulation as well heightened public scrutiny and pressure. There exists evidence in support of the theory that ESG-conscious firms that practice sustainably tend to financially outperform their peers. This study employs a quantitative research methodology, using variations of panel regression models to investigate the ESG-corporate financial performance (CFP) relationship. Privately held proprietary ESG scores are used as a proxy for ESG performance and financial data is obtained from Bloomberg in order to assess financial performance. The study does not find statistically significant evidence of a relationship between firm ESG performance and financial performance. Contrasting results emerge from the study, with positive relationships and correlation coefficients found between both the ESG performance of firms and their annual stock return, as well as the ESG performance and return on assets (ROA) ratio. A negative relationship and correlation were found to exist between firm ESG performance and their price earnings ratio. These contradicting results lead to a conclusion that no relationship exists between ESG performance and CFP. Significant evidence was however found regarding certain firm characteristics leading to firms having higher ESG performance. Results show that the larger firms with greater financial leverage are higher ESG performers relative to their peers. This may imply that in order for ESG practices to be effective, firms themselves should be of a sufficient size and have access to a large amount of debt to fund relevant activities. It is recommended that further research be performed on the driving forces behind a firm's ESG performance, and the various factors that contribute most towards it, including varying levels of access to debt.